1995
DOI: 10.1002/ejsp.2420250204
|View full text |Cite
|
Sign up to set email alerts
|

Prototypical similarity, self‐categorization, and depersonalized attraction: A perspective on group cohesiveness

Abstract: In contrast to traditional approaches that widely equate group cohesiveness with interpersonal at traction, self-categorization theory argues that self-categorization depersonalizes perception in terms of

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

8
84
0
2

Year Published

1998
1998
2013
2013

Publication Types

Select...
7
3

Relationship

2
8

Authors

Journals

citations
Cited by 125 publications
(94 citation statements)
references
References 34 publications
8
84
0
2
Order By: Relevance
“…When an in-group member meets or exceeds prior expectations with respect to unobserved attributes, his or her relationships with in-group members are stronger (Hogg et al 1995).…”
Section: Arrangements (Caldiera and Patterson 1987)mentioning
confidence: 99%
“…When an in-group member meets or exceeds prior expectations with respect to unobserved attributes, his or her relationships with in-group members are stronger (Hogg et al 1995).…”
Section: Arrangements (Caldiera and Patterson 1987)mentioning
confidence: 99%
“…Kahl 2005;Hicks 2006;Rossteutscher 2009), which lead to a "pronounced anti welfare-state position" of churches and parties (Manow 2002:206). Research on social identity has shown that individuals who self-categorize themselves into a social group will adapt the norms, world-views, and preferences that are dominant in that group (Tajfel 1981;Hogg et al 1995;Huddy 2001).…”
mentioning
confidence: 99%
“…They become based on perceived prototypicality (called social attraction) rather than idiosyncratic preferences or personal relationships (called personal attraction), which is the social attraction hypothesis (Hogg, 1992(Hogg, , 1993; for direct empirical tests, see Hogg, Cooper-Shaw, & Holzworth, 1993;Hogg & Hains, 1996Hogg & Hardie, 1991;Hogg, Hardie, & Reynolds, 1995). Ingroup members are liked more than outgroup members because the former are perceptually assimilated to a relatively positive ingroup prototype, or because their prototypical similarity to self is perceptually accentuated, or because self-liking (self-esteem) is extended to embrace people who are to some extent now viewed as prototypical extensions of self.…”
Section: Social Attraction Hypothesismentioning
confidence: 99%